Pengaruh Variasi Persentase Campuran Arang Tempurung Kelapa dengan Batubara dalam Pembuatan Briket Biocoal Terhadap Sifat Fisik dan Laju Pembakaran - Maktub, Zana Azalia; Sugianti, Cicih; Wibowo, Sasongko Aji (Jurnal Agricultural Biosystem Engineering, 2024)
This study aims to examine the effect of varying percentages of coconut shell charcoal mixed with coal on the physical properties and combustion rate of biocoal briquettes. The briquettes were made with four variations of coconut shell charcoal percentages: 16%, 31.9%, 47.7%, and 63.7%. The results revealed that briquette density tended to decrease with an increasing percentage of coconut shell charcoal, except for the 63.7% mixture, which showed an anomaly with higher density. Mechanical strength, including tensile and compressive strength, decreased as biomass increased due to the weaker mechanical properties of coconut shell charcoal compared to coal. The combustion rate decreased with higher biomass percentages, with longer combustion times for higher biomass content due to the higher calorific value of coconut shell charcoal. Biocoal briquettes demonstrated better combustion efficiency than regular briquettes but were still inferior to super briquettes and pure coal briquettes. This study highlights the potential of biomass-coal mixtures as an alternative, environmentally friendly, and efficient energy source. Keywords: Biocoal Briquettes, Coal, Coconut Shell Charcoal, Combustion Rate. Density.